VD_FINDINFO HC / 2024 / 85 vom 23. Mai 2024 - VD Tribunal cantonal (2024)
MESURE PROVISIONNELLE, RETRAIT DU DROIT DE GARDE, PLACEMENT D'ENFANTS | 176 al. 3 CC, 310 al. 1 CC, 276 al. 1 CPC (CH), 311 al. 1 CPC (CH)